Human Oncogenic Herpesvirus and Post-translational Modifications – Phosphorylation and SUMOylation - Chang, Pei-Ching; Campbell, Mel; Robertson, Erle S. (Frontiers in Microbiology, 2016)
Pathogens, especially viruses, evolve abilities to utilize cellular machineries to facilitate their survival and propagation. Post-translational modifications (PTMs), especially phosphorylation and SUMOylation, that reversibly modulate the function and interactions of target proteins are among the most important features in cell signaling pathways. PTM-dependent events also serve as one of the favorite targets for viruses. Among the seven unambiguous human oncogenic viruses, hepatitis B virus (HBV), hepatitis C virus (HCV), Epstein-Barr virus (EBV), Kaposi’s sarcoma-associated herpesvirus (KSHV), human papillomavirus (HPV), Human T lymphotrophic virus-1 (HTLV-1), and Merkel cell polyomavirus (MCPyV), two are herpesviruses. The life cycle of herpesviruses consists of latent and lytic phases and the rapid switch between these states includes global remodeling of the viral genome from heterochromatin-to-euchromatin. The balance between lytic replication and latency is essential for herpesvirus to maintain a persistent infection through a combination of viral propagation and evasion of the host immune response, which consequently may contribute to tumorigenesis. It is no surprise that the swift reversibility of PTMs, especially SUMOylation, a modification that epigenetically regulates chromatin structure, is a major hijack target of the host for oncogenic herpesviruses. In this brief review, we summarize the varied ways in which herpesviruses engage the host immune components through PTMs, focusing on phosphorylation and SUMOylation.